A Study Over Survey On The Life Style Of Young Students (International Journal of Scientific Research and Management (IJSRM), 2017)
The survey has been conducted over 598 students selected from 5 different schools of Palampur & Baijnath Tehsil of Distt. Kangra, H.P from class 11th and 12th having same social and cultural background. The students were distributed a questionnaire proforma containing 19 questions. In this study it was found that boys are leading the girls in use of mobile phones, internet activities, watching television, playing video games and bike driving. Most of the students who have accepted for driving the bike with maximum speed over 50 km/ hr on hilly roads of Himachal Pradesh were found below the age of 18 years, which is against driving laws. Thoughts of committing suicide have also been accepted by the students. Most students were found aware about their career. The most favoured career option by boys was Indian Armed Forces and for girls to be a doctor. About 91% students have preferred government job. On a question about the barrier in achieving their career goal maximum students had accepted their bad luck as a barrier in achieving their career goal. Most of the students have chosen their parents & teachers as their role model.